A sociotechnical order for the umma: connecting Islam and technology in Suharto's Indonesia. (2nd April 2020) - Moon, Suzanne
ABSTRACT: This article explores narratives connecting Islam and technology that arose in Indonesia during the New Order period (1965–1998). These public discussions defined technological work, especially work in high technology, as a vital spiritual and economic arena for Indonesian Muslims. By asserting technology as a site for spiritual action, Indonesian Islamic activists offered a redefinition of economic development intended to alter both its goals and the character of participation in the development enterprise. In doing so, they framed technological activity as a crucial form of moral agency. Embracing the postsecular turn in historical scholarship which emphasizes attention to the ongoing social processes which define religiosity and secularity, this article investigates how religion and technology are entangled in contemporary Indonesia.